Evolution of structure and improvement in dielectric properties of praseodymium substituted YFeO3 nanomaterials synthesized via a sol-gel auto-combustion method. Issue 5 (1st March 2021) - Asif, Muhammad; Khan, Muhammad Azhar; Atiq, Shahid; Alshahrani, Thamraa; Mahmood, Q.; Kattan, Nessrin A.; Manzoor, Alina
Abstract: In this work, Y 1 − x Pr x F e O 3 ( 0 ≤ x ≤ 0.16 ) ceramics were fabricated via the auto-combustion sol-gel method. X-ray diffraction (XRD), scanning electron microscopy (SEM) associated with EDS mapping, and Fourier transform infrared spectroscopy (FTIR) were employed for structural and morphology analysis. The substitution of praseodymium (Pr) modified the orthorhombic structure into a hexagonal structure. However, small traces of Fe2 O3 and Y2 O3 appeared in all samples. The lattice constant 'a' was increased from 3.523 to 5.530 Å upon substitution up-to x = 0.12, afterward this started to decrease from 5.530 to 5.529 Å. Pure orthorhombic YFeO3 (o-YFeO3 ) has cell volume 223.61 (Å 3 ), while the cell volume of Pr substituted hexagonal YFeO3 (h-YFeO3 ) showed a decreasing trend (125.61–125.43 Å). Bulk density was thoroughly decreased from 5.009 to 4.634 (g/cm 3 ) by increasing the Pr concentration. Frequency dependence of the dielectric behavior was investigated at room temperature in a comprehensive frequency range of 1 MHz ~ 3 GHz. SEM results exhibited the average grain size 149.28 nm, 66.78 nm, and 69.36 nm for the samples 0.00, 0.08, and 0.16, respectively. The identification of o-YFeO3 was confirmed by two main absorption bands ν1 (449.86 cm -1 ) and ν2 (567.12 cm -1 ) and these bands indicate a clear shift upon the addition of Pr. The force constant of absorption bands at tetrahedral and octahedral sites showed increasing trend and this ranges from 1.633dyn/cm 2 x10 5 to 1.912dyn/cm 2 x10 5 and 2.818dyn/cm 2 x10 5 to 8.832dyn/cm 2 x10 5, respectively. The substitution of Pr significantly enhanced the dielectric constant. The shifting of peaks at higher frequencies demonstrates that an increase of dopant concentration resulted in the shifting of peaks that may follow the Maxwell-Wagner-Sillars polarization mechanism. Pr substituted YFeO3 exhibited microwave frequency response in a range of 1.6 GHz–2.9 GHz which might be suitable for high-frequency applications.